Pengaruh Attitude, Norma Subjektif, Perceived Behavior Control Terhadap Niat Mengeluh Karyawan PT. Sinar Murni Indopriinting - Aizzatul Laila; Wahyu Eko Pujianto (Politeknik Kampar, 2023)
This study aims to determine whether attitude, subjective norms and perceived behavior control affect the intention to complain at PT Sinar Murni Indoprinting employees. This study used quantitative research where researchers used surveys and distributed questionnaires which were then tested through SmartPLS 4.0 software and made production employees as research samples. the results of data analysis found that attitude, subjective norms, and perceived behavior control affect the intention to complain to employees.